Consumer Perception towards Different Media Options: An Empirical Study of Rural V/s Urban Perspective - Makkar, Urvashi; Dhyani, Vijendra (Indian Journal of Marketing, 2010)
Indian media market is one of the largest in the world by virtue of its reach, access and business potential. This volatile industry has made several changes in its performance model to achieve success in an unprecedented competitiveness. Indian newspapers have grown steadily along with the other media. The Internet, which was once assumed to eat away newspapers, has not been able to affect the newspaper business till date. The socio-economic fabric of India, which is so different, makes room for sustenance of all forms of media. Media amalgamation and interdependence are at the root of success of media industry. This paper analyzes the different factors that affect the choice and preferences of media vehicles in rural and urban consumers. The research also emphasizes on the fact that how important the media is in consumer’s buying decision process, that is surging ahead is the credit cards industry. Today, the Indian population feels that a wallet without a card is empty. During the last one decade, there has been an exponential growth in the issue of credit cards and their usage.